Thawing out: Therapy through theatre with Canadian military veterans. (February 2019) - Belliveau, George; Cook, Christopher; McLean, Blair; Lea, Graham W.
Highlights: Veterans were motivated to participate to help other veterans. Theatre performance has therapeutic and personal benefits for veterans. Rehearsal and performance allows physicalizing and release of trauma. Theatre making creates spaces for veterans to rebuild social connectedness. Abstract: This article explores Contact!Unload, a theatre project in which military veterans, with the support of artists, community members, and counsellors, performed what it means to transition back to civilian life after serving their country. The play features therapeutic enactment, an approach to addressing psychological injuries veterans might face while serving. Various iterations of the play have been performed across Canada and the UK, each featuring a minimum of four veterans. Through extensive interviews with veterans who performed in the production, this article unpacks how creating, rehearsing, and performing in Contact!Unload contributed to personal change. Their goal of participating in the play was focused on helping other veterans who might be suffering from posttraumatic stress injuries, showing successful approaches to coping with service related trauma. However, an unexpected discovery during the theatre process was how their engagement with art-making and performing extended their own therapy, leading to significant personal changes for a number of the performing veterans.